Hubungan Asupan Natrium dengan Kejadian Hipertensi di Posyandu Lansia Desa Tegowangi Kecamatan Plemahan Kabupaten Kediri - Dwi Reka Aprilliyanti; Frenky Arif Budiman (Nutriology : Jurnal Pangan,Gizi,Kesehatan, 2020)
Adequate intake of sodium but causes hypertension in the elderly this is because basically elderly have a history of hypertension. Effect of Sodium intake on the occurrence of hypertension occurs through increased plasma volume, cardiac output, and blood pressure. Excessive consumption of Sodium causes the concentration of Sodium in the extracellular fluid to increase. To normalize it, the intracellular fluid is pulled out, so that the extracellular fluid increases. Increased extracellular fluid increases blood volume. Analyzing Relationship of Sodium Intake with Hypertension Incidence at Elderly Posyandu Tegowangi village Plemahan Sub-district of Kediri. The study was conducted at Elderly Posyandu addresses Tegowangi district of Plemahan Kediri Regency. Sample using random sampling. Research subjects were elderly who had high blood pressure. There was no significant relationship between sodium intake with hypertension ( 0.895 > 0.05 ) in Posyandu Lansia Tegowangi, Plemahan sub-district of Kediri. Because of other factors tha can affect the occurrence of hypertension in elderly. There is no Relationship of Sodium Intake with Hypertension Incidence at Elderly Posyandu Tegowangi village Plemahan Sub-district of Kediri. There needs to be counseling conducted posyandu about factors causing hypertension and foods high in sodium, to prevent the occurrence of hypertension in elderly.